ANALISIS PERAN KELUARGA TERHADAP PENCEGAHAN PENYALAHGUNAAN NARKOTIKA DAN SEKS BEBAS PADA ANAK DAN REMAJA DI DESA PAGERWANGI - Putra Pratama, Rexa Putra; Setiadi, Elly Malihah; Wahyuni, Sri (Jurnal Analisa Sosiologi, 2024)
The family is the first socialization agent that children get since they are born into the world. The role of the family is very significant in the formation of a child's character. One of them is the role in overcoming drug abuse behavior and free sex among children and adolescents. This study uses a qualitative approach with phenomenological design, exploring the perceptions of children and adolescents towards drug abuse and free sex. The determination of informants is done through purposive sampling, while data sources are obtained from observation, unstructured interviews, documentation, and literature studies. Triangulation of data and theory is used for data validity, by integrating Structural Functionalism theory from Talcott Parsons and conflict theory from Karl Marx in analyzing how the role of family in Pagerwangi Village contributes to preventing drug abuse and free sex behavior in children and adolescents.   Strategic steps including passive observation and unstructured interviews are conducted to create a natural environment and gain in-depth information. The results showed that drug abuse and free sex in children and adolescents in Pagerwangi Village were caused by lack of parental supervision, low communication intensity, and inequality of access to information, so that families have not been optimal in carrying out social control functions. Intensive measures are needed, such as building a communicative family environment, providing age-appropriate education, and strengthening equal access to information to create a stable environment.